Kemampuan Pengusaha Dari Perspektif Orientasi Kewirausahaan dan Konsep Penjualan Di Masa New Normal - Anam, Choirul; Survival, Survival; Iswari, Hanif Rani (Jurnal Ilmu Manajemen, 2021)
This paper aims to be able to build a construct based on empirical studies, so that it will become the basis for making policies and programs in order to maintain and develop business ventures in the new normal era. This paper uses a qualitative approach with a constructivist paradigm. The research design used is grounded theory. Research setting in Capture Chicken Malang Geprek. The intended informants are the owners and customers of Malang Geprek Catched Chicken. Data analysis using open coding, axial coding, and selection coding. Data validity uses data credibility. The research findings show that an entrepreneur can develop and maintain a business if he has the passion and ability, besides that there is an entrepreneurial orientation: risk-taking, pro-active, and innovation in the sale of goods so as to improve business performance. The need for emphasis on sales such as goods, prices, services, places of sale, systems and sales techniques.